ANALISIS PERMINTAAN KEDELAI DI INDONESIA - Septi Rostika Anjani; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
This study aims to analyze the factors that influence the demand of soybean in Indonesia. The research method uses descriptive analysis of secondary data which includes the price of imported soybeans, the price of chicken, per capita  income,  the rate of inflation and import tariff policy  year period 1980-2013 which sourced from FAO  and  other  sources.  Estimation  of  demand  function  using  multiple  linear regression  analysis  were  transformed  in  the  form  of  natural  logarithm.  Regression analysis showed that soybean demand in Indonesia was influenced partially by prices of chicken, per capita income, and the rate of inflation. The price elasticity of demand of soybean in Indonesia is inelastic, that is equal 0,22. While the income elasticity of demand  for  soybeans  is  positive  which  means  that  soy  is  a  staple  item  for  the Indonesian people.